Suppressive Effect of Autocrine FGF21 on Autophagy-Deficient Hepatic Tumorigenesis - Kim, Jinyoung; Lee, Soyeon; Lee, Myung-Shik (Frontiers in Oncology, 2022)
Mice with hepatocyte-specific deletion of autophagy-related 7 (Atg7ΔHep mice) develop hepatoma, suggesting that autophagy deficiency could be a factor in the initiation of tumorigenesis. We have shown that FGF21 is induced as a ‘mitokine’ when Atg7 is disrupted in insulin target tissues such as the liver, which could affect systemic metabolism through endocrine activity. Since FGF21 or other endocrine FGF such as FGF19 can affect tumor growth, we hypothesized that FGF21 produced by Atg7-knockout (KO) hepatocytes may affect behavior of Atg7-KO hepatoma in an autocrine manner. We, thus, crossed Atg7ΔHep mice with systemic Fgf21-KO (Fgf21-/-) mice to generate Atg7ΔHepFgf21-/- mice. The number and size of hepatoma of Atg7ΔHep mice were significantly increased by additional Fgf21 KO. Proliferation of Atg7-KO hepatocyte was significantly increased by Fgf21 KO. pYAP1/YAP1 representing YAP1 degradation was significantly decreased in the liver of Atg7ΔHepFgf21-/- mice compared to Atg7ΔHepFgf21+/+ mice. Consistently, expression of YAP1/TAZ downstream genes was significantly increased in the liver of Atg7ΔHepFgf21-/- mice compared to Atg7ΔHepFgf21+/+ mice, which can explain increased size of hepatoma in Atg7ΔHepFgf21-/- mice. Accumulation of ROS and ROS-mediated DNA damage were increased in the liver of Atg7ΔHepFgf21+/+ mice, which was further aggravated by additional Fgf21 KO probably due to the absence of positive effect of FGF21 on mitochondrial function, explaining increased number of hepatoma in Atg7ΔHepFgf21-/- mice compared to Atg7ΔHepFgf21+/+ mice. These results showing that FGF21 produced by autophagy-deficient hepatocytes could have autocrine or paracrine effects on the number and proliferation of autophagy-deficient hepatoma, suggest that hormones or factors released from autophagy-deficient tumors can influence behavior or prognosis of the tumor in addition to the effects on host metabolism.